2017
DOI: 10.1053/j.ajkd.2017.01.045
|View full text |Cite|
|
Sign up to set email alerts
|

Kidney Injury and Repair Biomarkers in Marathon Runners

Abstract: Background Investigation into strenuous activity and kidney function has gained interest given increasing marathon participation. Study Design Prospective observational study Setting & Participants Runners participating in the 2015 Hartford Marathon Predictor Completing a marathon Outcomes Acute kidney injury (AKI) as defined by AKI Network (AKIN) criteria. Stage 1 AKI was defined as 1.5- to 2-fold or 0.3 mg/dL increase in serum creatinine within 48 hours of day 0 and stage 2 was defined as a > 2- to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 53 publications
11
113
1
5
Order By: Relevance
“…; Mansour et al. ). However, the postexercise uncorrected uNGAL level after prolonged exercise found in our study (16.5 ng/mL) was lower compared to previous studies with postexercise values ranging from 37.6 to 47.0 ng/mL (McCullough et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Mansour et al. ). However, the postexercise uncorrected uNGAL level after prolonged exercise found in our study (16.5 ng/mL) was lower compared to previous studies with postexercise values ranging from 37.6 to 47.0 ng/mL (McCullough et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Mansour et al. ). This might be explained by our relatively young population (23 years vs. >38 years), and the shorter period of exercise in our study (137 min vs. >240 min).…”
Section: Discussionmentioning
confidence: 99%
“…; Mansour et al. ) increases urinary excretion of KIM1 (uKIM1) and NGAL (uNGAL). It has been suggested that exercise intensity is the most important factor that impacts on exercise‐induced kidney stress.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, a number of new biomarkers have been identified to detect acute kidney injury in an early stage, of which Kidney Injury Molecule-1 (KIM1) and Neutrophil gelatinaseassociated lipocalin (NGAL) are best known (Mishra et al 2005;Bonventre 2008;Devarajan 2008). Previous studies suggested that a single bout of short-term high intensity exercise (Junglee et al 2012) or completing a (ultra)marathon (McCullough et al 2011;Lippi et al 2012;Mansour et al 2017) increases urinary excretion of KIM1 (uKIM1) and NGAL (uNGAL). It has been suggested that exercise intensity is the most important factor that impacts on exercise-induced kidney stress.…”
Section: Introductionmentioning
confidence: 99%
“…O aumento rápido de TFF3 no presente estudo é provavelmente devido à lesão tubular proximal e distal induzida pelo HIIRT, e pode estar associado a início de processo regenerativo das células epiteliais. Um estudo prospectivo observacional em 22 corredores de maratona também encontrou aumento precoce nos biomarcadores de reparação tubular renal após exercício (glicoproteína 39 da cartilagem humana -YKL-40 e proteína 1 quimioatratora de monócitos -MCP-1) 24 .…”
Section: Biomarcadores Urinários De Lesão Renalunclassified